Stable development of rural territories: method of estimation and typologization (on the example of Krasnoyarsk region) - R. M. Gazizov (Russian Journal of Economics and Law)
Objective: basing on the existing methods, to propose the improved method of estimating rural territories, which would allow to estimate the “stability” of the territory, and to group rural territories by types. Methods: abstract-logic, mathematical and statistical methods. Results: The author has elaborated the method of rural territories’ stable development estimating, basing on which, the typologization of municipal districts of Krasnoyarsk region was made, which improves the development policy of rural territories. Scientific novelty: The elaborated method allows not only to define the level of stable development of rural territories in general, but gives an opportunity to define the development level of a certain sphere of society, its sectors, which allows to carry out the deeper typologization of the regions’ stability (within a certain type). Practical value: By calculating the integral indicator of the stable development of rural territories, the municipal districts of Krasnoyarsk region were divided into 3 types: highly stable, of intermediate stability and unstable. Such division promotes the more detailed elaboration of development programs and, in general, improving the development policy of rural territories.